A PVC plasticization electrically active laminated metamaterial with tunable sound insulating performance. (15th October 2022) - Wang, Chang; Li, Rui; Zhu, Zicai; Wu, Jiu Hui; Ma, Fuyin
Highlight: Electroactive polymer PVC is introduced into the study of active acoustic metamaterials. The characteristics of adjustable damping and variable stiffness of the laminated structure is highlighted in the tunable sound insulation. The characteristics of low voltage and rapid response determine that it has broad application prospects in sound insulation. Abstract: In this paper, we introduce an electrically driven laminated active acoustic metamaterial with PVC plasticization, which the structure is composed of electroactive PVC gel membrane, wire mesh electrodes, and conductive fabric in a sandwich form, that can achieve excellent sound-damping performance with tunable sound insulation. Compared with the previous tunable acoustic metamaterial, this structure requires lower driving voltage and better sound insulation performance. The specific researches are as follows: Firstly, we studied the strain rate of different laminated structure parameters after applying voltage was explored through experiments, and the design parameter combination with better strain rate was obtained by comparing the results. Then, the sound insulation performance of the laminated structure before and after the application of the electric field was studied, and it was concluded that the structure had better adjustable stiffness and damping characteristics under the action of the electric field, and improved the sound insulation performance in a wide frequency range. This provides a new way of adjustable sound insulation, which is expected to be used in heavy equipment such as automobiles.